Analisis Pengukuran Kinerja Operasional Rumah Sakit Bakti Timah Pangkalpinang dengan Pendekatan Balanced Scorecard - Medinal Medinal (Politeknik Negeri Bengkalis, 2021)
This study is aim to analyze of Operational Performance Measurement using Balanced Scorecard method. Â Subject of this research is RSBT Pangkalpinang. This balanced scorecard is a tool that showed the hospital performance based on four perspectives namely financial, customer, internal business process, and learning and growth perspective. This research uses a quantitative-descriptive method. This study using primary and secondary data from 2018-2020. Primary data collection techniques through the distribution of questionnaires and interviews with respondents.Â The results of the analysis prove that the overall operational performance assessment at the RSBT Pangkalpinang Â uses a balanced score card that is satisfying and has a good performance mesurement.